Intelligent IoT Enable Fire Hazard Detector Device and Apps - Nor Azhar, Ahmad; Rahmah, Mokhtar; Roslina, Abd. Hamid; Fauziah, Zainuddin; Amirul Husni, Abd. Ghaffar (2019)
Fire hazard detection is a crucial part and one of the most critical elements in home protection. However, due to a wide variety of devices, domestic consumer failed to choose the right, reliable, and sustainable choice. Furthermore, most of the market devices did not follow the guidelines by SIRIM, since it comes from China without proper investigation on reliability. The development of the proposed method closely monitored by the Fire and Rescue Department of Malaysia. While the application and monitoring of device performance monitor by Fire Preventors Society. As to date, they are sensors in fire hazard detector; smoke, flame and gasses. We try to harmonise, those three into production rules, to avoid false alarm. Also, an addition of carbon monoxide, temperature and humidity are added to reduce the false alarm prevention mechanism to 100% of reliability. Implementation in pilot site around Kuantan and Johor Bahru show reliability, and trustworthy evaluation exceeds 90%, based on questionnaires answered by the tester for the period of the first six months.